A feasibility study on biological nitrogen removal (BNR) via integrated thiosulfate-driven denitratation with anammox. (October 2018) - Qian, Jin; Zhang, Mingkuan; Wu, Yaoguo; Niu, Juntao; Chang, Xing; Yao, Hairui; Hu, Sihai; Pei, Xiangjun
Abstract: To exploit the advantages of less electron donor consumptions in partial-denitrification (denitratation, NO3 − → NO2 − ) as well as less sludge production in autotrophic denitrification (AD) and anammox, a novel biological nitrogen removal (BNR) process through combined anammox and thiosulfate-driven denitratation was proposed here. In this study, the ratio of S2 O3 2− -S/NO3 − -N and pH are confirmed to be two key factors affecting the thiosulfate-driven denitratation activity and nitrite accumulation. Simultaneous high denitratation activity and substantial nitrite accumulation were observed at initial S2 O3 2− -S/NO3 − -N ratio of 1.5:1 and pH of 8.0. The optimal pH for the anammox reaction is determined to be 8.0. A sequential batch reactor (SBR) and an up-flow anaerobic sludge blanket (UASB) reactor were established to proceed the anammox and the high-rate thiosulfate-driven denitratation, respectively. Under the ambient temperature of 35 °C, the total nitrogen removal efficiency and capacity are 73% and 0.35 kg N/day/m 3 in the anammox-SBR. At HRT of 30 min, the NO3 − removal efficiency could achieve above 90% with the nitrate-to-nitrite transformation ratio of 0.8, implying the great potential to apply the thiosulfate-driven denitratation & anammox system for BNR with minimal sludge production. Without the occurrence of denitritation (NO2 − → N2 O → N2 ), theoretically no N2 O could be emitted from this BNR system. This study could shed light on how to operate a high rate BNR system targeting to electron donor and energy savings as well as biowastes minimization and greenhouse gas reductions. Highlights: A novel S2 O3 2− -driven denitratation & anammox system was proposed for high-rate BNR. Low sludge yield and less electron donor consumption could be achieved. S2 O3 2− -S: NO3 − -N and pH affect denitratation activity and NO2 − accumulation. Transformation ratio of NO3 − to NO2 − was above 0.8 at HRT of 30 min in UASB. TN removal capacity was 0.35 kg/d/m 3 by anammox at HRT of 6 h.